Green Synthesis AgNPs Immobilized to Whatman Paper Using Chromolaena odorata Extract and Its Application as Photocatalyst - Kiki Firanita; Syamsul Hidayat; Fadhli Dzil Ikram; Syamsul Bahtiar; Emsal Yanuar (Universitas Negeri Malang, 2022)
Synthesis and immobilization of silver nanoparticles (AgNPs) to Whatman paper carried out using Cromolaena odorata extract irradiated by sunlight. The UV-Vis shows silver nanoparticles successfully formed from AgNO3 1 mM, 2 mM, and 3 mM with the absorption peaks at 455 nm, 452 nm, and 451 nm, respectively. The SEM shows AgNPs are spherical with an average particle size are 60.45 nm, 63.19 nm, and 68.42 nm, respectively. The EDX spectrum shows the composition of silver immobilized to Whatman paper increase with increasing concentration of 10.14Wt%, 64.48Wt%, and 70.48 Wt%, respectively. AgNPs/Whatman paper has a cubic crystal structure, space group Fm-3m, lattice parameter (a) 4.0862 Ǻ and crystal size of 42.94 nm. FTIR reach peaks at 520.78 cm-1 and 1,059 cm-1 explains the vibration of the Ag-O bonds indicated the formation of AgNPs. Furthermore, the photocatalyst ability for dye degradation was evaluated using methylene blue 10 ppm under sunlight for 6 hours. The result shows a changed colour to fade and decreases the absorbance ability of methylene blue. Therefore, it can be concluded that green synthesis and immobilization of AgNPs/Whatman paper have a potential to be applied as photocatalyst materials for dye degradation.DOI: 10.17977/um024v7i12022p006